Halogenated flame retardants in Irish waste polymers: Concentrations, legislative compliance, and preliminary assessment of temporal trends. (15th September 2022) - Drage, Daniel; Sharkey, Martin; Al-Omran, Layla Salih; Stubbings, William A.; Berresheim, Harald; Coggins, Marie; Rosa, André Henrique; Harrad, Stuart
Abstract: Halogenated flame retardants (HFRs) were measured in 470 waste plastic articles from Ireland between 2019 and 2020. We identified articles containing concentrations of polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCDD), and tetrabromobisphenol-A (TBBP-A) exceeding European Union limits. Enforcement of existing limits of 1000 mg/kg will render an estimated 3.1% (2800 t) of articles in the waste categories studied unrecyclable, increasing to: 4.0, 4.9, and 5.6% if limits were reduced to 500, 200, and 100 mg/kg respectively. Meanwhile, enforcing limits of 1, 000, 500, 200, and 100 mg/kg will respectively remove 78, 82, 84, and 85% of PBDEs, HBCDD, and TBBP-A present in such waste. Other FRs targeted were detected infrequently and predominantly at very low concentrations. However, 2, 4, 6-tris(2, 4, 6-tribromophenoxy)-1, 3, 5-triazine (TTBP-TAZ) was detected in 3 display/IT product samples at 14, 000 to 32, 000 mg/kg, indicating elevated concentrations of FRs used as alternatives to PBDEs and HBCDD, will likely increase in future. Comparison with data for Ireland in 2015–16, revealed concentrations and exceedances of limits for PBDEs, HBCDD, and TBBP-A were similar or have declined. For end-of-life vehicle fabrics and foams, HBCDD and ΣPBDE concentrations declined significantly (p < 0.05) since 2015–16. Moreover, ΣPBDE concentrations in waste small domestic appliances are significantly lower in 2019–20, with a similarly significant decline for TBBP-A in waste IT and telecommunications articles. In contrast, HBCDD concentrations in waste extruded polystyrene increased significantly between 2015–16 and 2019–20. For other waste categories studied, no statistically significant temporal trends are evident (p > 0.05). Fewer samples exceeded PBDE and HBCDD limits in 2019–20 (7.8%) than 2015–16 (8.7%), while exceedances for TBBP-A fell from 2.4% in 2015–16 to 0.57% in 2019–20. While comparison between the 2015–16 and 2019-20 datasets provide a preliminary indication of changes, further monitoring is required if the impact of legislation designed to eliminate HFRs from the waste stream is to be fully evaluated. Graphical abstract: Image 1